The Influence of Independent Curriculum and Classroom Management on Elementary Students’ Learning Outcomes in Ogan Ilir - Siti Marhamah Winarti; Nur Ahyani; Nurlina Nurlina (International Journal of Educational Development, 2025)
This study investigates the influence of the implementation of the Independent Curriculum (Kurikulum Merdeka) and classroom management on student learning outcomes in public elementary schools across the Indralaya District, Ogan Ilir Regency. Employing a quantitative research method with a correlational approach, data were collected through questionnaires distributed to teachers and through documentation of student performance. The findings reveal that both the application of the Independent Curriculum and effective classroom management significantly contribute to improving student learning outcomes. The study emphasizes the importance of teacher competence in managing classrooms and delivering the curriculum in a way that promotes student engagement and academic achievement. These results highlight the need for continuous professional development and support in implementing educational reforms at the elementary level.